(untitled) (Dimensión Empresarial, 2022)
The objective of this research was to determine the level of use of IT in SMEs in Mexico City and establish its relationship with performance, the characteristics of the entrepreneur and the characteristics of the company. Data from 300 entrepreneurs were collected with a direct structured questionnaire, performing a descriptive and correlational analysis. It was found that SMEs in Mexico City use basic IT, business performance is related to the use of the website and computer equipment. Also, it was established that there is a relationship between IT and the level of studies, where the higher the level of studies, the higher the level of use of IT; Likewise, a relationship was established with size, finding that the largest ones are constituted as commercial companies and are of a non-family type, make use of IT in their business management.